The PAiCE (Prioritising Agronomy in Changing Environments) Tool for empowering climate adaptation initiatives - Brown, B.; McDonald, A. J. (2022)
The anticipated impacts of climate change on cropping systems are well characterized for many regions. Comparatively less attention has been given to the prioritization of strategies that will help communities adapt to these changes at different time-scales for action. There are no adaptation 'silver bullets', and options must be considered in a broad context that often only emerges from participatory appraisal. The PAiCE framework provides a process though which stakeholders can collaboratively learn and collectively prioritise adaptation options that respond to the most pressing contemporary and projected climate challenges while identifying knowledge gaps and key areas of uncertainty.